Discriminant analysis during the financial security benchmarking of PJSC "Kompleksne pidpryiemstvo shyrokoprofilnoho budivnytstva-2" - Izmailova, K.V. (Ways to Improve Construction Efficiency, 2020)
The authors in the research article consider benchmarking as an effective management tool. This method usually is used in marketing, marketing research, but benchmarking can also be used to increase the economic efficiency of financial management of the company. The article identifies the principles and peculiarities of benchmarking analysis, the authors propose new stages of benchmarking on the basis of generalization of approaches of different researchers for this issue. Researchers use methods such as cluster analysis, factor analysis, component analysis, regression analysis and discriminant analysis, because there is a need to divide the objects of research into separate groups according to the main strategic priorities. The authors choose discriminant analysis, which was performed using MS Excel software. Benchmarking analysis of financial security was conducted on three indicators - coverage ratio (from the group of liquidity indicators), concentration coefficient of equity (from the group of financial stability indicators)and ROS (from the group of profitability indicators). The sample of competing companies was formed, consisting of 15 joint-stock companies of Kyiv region and Kyiv with the main activity - construction of residential and non-residential buildings. Two sub-samples have been identified, each containing 4 objects: the first group includes the best companies, where the threat of financial crisis is not high, while the second group includes the worst companies with inefficient financial management. Subsamples formation criterias are the maximum and minimum of the average value of three indicators. Efficiency of financial management, probability of financial crisis and getting of benchmarking companies in a particular group is determined according to the discriminant analysis with the help of an integrated indicator.